Investing cash transfers to raise long term living standards - Gertler, Paul J. 1955- (Policy research working paper, 2006)
"The authors test whether poor households use cash transfers to invest in income generating activities that they otherwise would not have been able to do. Using data from a controlled randomized experiment, they find that transfers from the Oportunidades program to households in rural Mexico resulted in increased investment in micro-enterprise and agricultural activities. For each peso transferred, beneficiary households used 88 cents to purchase consumption goods and services, and invested the rest. The investments improved the household's ability to generate income with an estimated rate of return of 17.55 percent, suggesting that these households were both liquidity and credit constrained. By investing transfers to raise income, beneficiary households were able to increase their consumption by 34 percent after five and a half years in the program. The results suggest that cash transfers to the poor may raise long-term living standards, which are maintained after program benefits end. "--World Bank web site